Muslim Identity in Media Projection - Miladiah, Istiq Nafi Naenal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
Media is a means of circulating information. Ideally, the media should factually report information or at least minimize gender bias and other agendas. In this case, the media's perspective on Muslim women can be said to be disparate. Reports related to Muslim women have different spotlight values ​​that trigger different views on Muslim identity. This research is qualitative research with a literature approach. In this study, it was found that the media projected Muslim women as commercial commodities, besides that there was a tendency for the media to frame Muslim women as a role that was powerless and seemed to ask for empathy. The media also labels Muslim women as superwomen who can manage the role of housewives as well as the responsibilities of children and families, so that it is constructed in the social order.